Bridging Pedagogical and Managerial Governance in Islamic Education: A Qur’anic Based Holistic Integration Model - dody pratama; Zahrotul Lathifah; Septina Cahyani Putri; Syifa Fauziah (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
This study examines the systemic crisis of pedagogical–managerial integration in Islamic educational institutions in Banjit District, Indonesia, characterized by fragmentation between Qur’anic–Hadith-based institutional visions and their implementation in instructional and governance practices. The research aims to (1) identify patterns of integration crisis, (2) measure the level and consistency of integration between pedagogical and managerial dimensions, and (3) formulate and empirically validate a holistic integration model grounded in Islamic values. A mixed-methods sequential explanatory design was employed. The qualitative phase involved in-depth interviews, observations, and document analysis with 24 informants, generating five major crisis themes through coding procedures. The quantitative phase surveyed 168 respondents using a 32-item Likert-scale instrument developed from qualitative findings (Cronbach’s Alpha = 0.89). Statistical analysis included Pearson correlation and simple linear regression. The results indicate that integration remains at a moderate level, with a strong positive correlation (r = 0.71) between pedagogical and managerial dimensions. Regression analysis shows that managerial integration explains 50% of the variance in pedagogical integration (R² = 0.50), representing a substantial effect size within educational research contexts. Theoretically, this study advances the construct of systemic integration in Islamic education by synthesizing Islamic epistemology with global theories of instructional leadership and whole-school reform. It proposes a holistic model consisting of value-based vision, curriculum integration, value-based supervision, integrated character evaluation, and transformative religious leadership. Practically, the findings highlight that sustainable instructional reform requires institutional restructuring to ensure coherence between values, governance, and classroom practice in contemporary Islamic education.